Reverberation indices in acoustic assessments of sacral structures - Engel, Z.; Kosała, K. (Archives of Acoustics, 2004)
The proposition of the acoustic assessment of interiors of sacral buildings by means of the single-numbered, global index of acoustic quality was given in this paper. The introduction of a uniform method is justified since none of the available methods addresses to a sufficient degree to the specificity of such interiors. The main partial index - the reverberation index - was discussed and applied to the tests in several catholic churches, where acoustic measurements were performed. The continuation of the research presented here will lead to the development of a new method especially suitable for the acoustic quality assessment of sacral buildings.